The Afrotropical genera of Psychodini: Redefinition of the tribe, first Afrotropical record of Perithreticus Vaillant, 1973 and description of Soeliella gen. nov. (Diptera: Psychodidae: Psychodinae) - Kvifte, Gunnar Mikalsen (Zootaxa, 2015)
Psychodini is redefined based on morphological characters and newly recognized homologies in the male genitalia. It is hypothesised that the ground-plan aedeagus of Psychodini consists of a symmetrical bipartite aedeagus flanked by paired, symmetrical parameres; which in many lineages have become asymmetrical via the differentiation of phallomeres and parameres and/or via reduction of one paramere. The Afrotropical genera of Psychodini are reviewed and a key for their identification is provided.        Perithreticus Vaillant, 1973 is recorded from Tanzania based on the new species Perithreticus anderseni sp. nov. The genus is redefined, characterised by an elongate symmetrical aedeagus with paired subtriangular parameres, and a broad M-shaped epiproct with a concave anterior margin. Soeliella gen. nov. is described to include Soeliella platypenis sp. nov.; characterised by the presence of paired subtriangular parameres and the distiphallic elements broadly fused into a spatulate plate. Rhipidopsychoda Vaillant, 1991 is raised from synonymy based on novel character interpretations. Rhipidopsychoda boettgeri (Wagner, 1979) comb. nov. is redescribed and a key to the world species is presented. The species Psychoda bilobata Quate, 1957 and Psychoda trilobata Quate, 1957, Psychoda morogorica Wagner & Andersen, 2007 and Philosepedon triangularis Eaton, 1913 are of dubious generic placement and need revision.